Sociometric Popularity, Perceived Peer Support, and Self-Concept in Adolescence - Fernández-Zabala, Arantza; Ramos-Díaz, Estibaliz; Rodríguez-Fernández, Arantzazu; Núñez, Juan L. (Frontiers in Psychology, 2020)
The objective of this study is to analyze the role that peer support plays in the incidence relationships between sociometric popularity and general self-concept based on sociometer theory. A total of 676 randomly selected secondary school students from the Basque Country (49.6% boys and 50.4% girls) between 12 and 18 years of age (M = 14.32, DT = 1.36) participated voluntarily. All of them completed a sociometric questionnaire (SOCIOMET), the Family and Friends Support Questionnaire (AFA-R), and the Dimensional Self-concept Questionnaire (AUDIM-33). Several models of structural equations were tested. The results indicate that sociometric popularity influences self-concept through the perceived social support of peers. These results are discussed within the framework of positive psychology and its practical implications in the school context.